PENGARUH PERUBAHAN DEBIT TERHADAP ANGKUTAN SEDIMEN PADA AMBANG GERIGI - Winda - Harsanti, ST., MT.; Suhartono - -; suselo utoyo (Jurusan Teknik Sipil, Politeknik Negeri Malang, 2019)
Gerigi weir was a modification of jigsaw weir, which the difference was in direction of curves. On jigsaw weir the curves were horizontally, but in gerigi weir the curves were vertically. The aim of this modification was sediment in upstream of weir could pass at certain speed of water. This research utilized open channel model. From this research would be known the possibility of gerigi weir in passing the sediment. Sharp weir would be used too as a comparison in flowing the sediment. In this research, some of different discharges were be used. Based on the observation, variation of the height of sediment on gerigi weir was more variable than on sharp weir. Ability to transport the sediment on gerigi weir was better than sharp weir. Keywords: gerigi weir, open channel flow, sediment